X-ray computed tomography for fast and non-destructive multiple pearl inspection. (November 2016) - Rosc, J.; Hammer, V.M.F.; Brunner, R.
Abstract: X-ray computed tomography displays a highly valuable nondestructive testing tool in various fields. A major disadvantage of this method comprises its high operating costs. Therefore, the reduction of the scanning times would be highly beneficial. Here, we demonstrate exemplarily for the testing of pearls the possibility to decrease the scanning times. The great diversity of pearls on the market, often of unclear origin, especially used for jewelry, demands non-destructive test methods for the fast and reliable classification and validation. We discuss the use of a nano-focus X-ray computed tomography (nf-XCT) system for fast three-dimensional characterization to distinguish between natural and cultured pearls. We test the approach not on individual pearls but for a more demanding task namely for a pearl necklace, that is multiple pearls on a strand. We show that with just one scan the 3D image data of the individual pearls within the whole necklace, which is composed of about 200 pearls can be scanned and reconstructed in only about 24 minutes. That is, we illustrate that nf-XCT as a inspection method is highly competitive to conventional radiography or radioscopy. The presented work also reveals possibilities for other fields like microelectronics etc. Highlights: We demonstrate the possibility to perform X-ray computed tomography on multiple pearls (pearl necklace) with one scan. We demonstrate that inspection times with proper settings of 24 min are feasible. We demonstrate that a sufficient image quality to distinguish between natural and cultured pearls is feasible. We show that this time scales are much faster than scanning times reported previously. The presented work also reveals possibilities for other fields like microelectronics etc.